THE ENVIRONMENTAL DEGRADATION IN THE EARTH CAUSED BY CONSUMERISM CULTURE IN ASTRO BOY THE MOVIE - ., FATIMAH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Fatimah. 2014.  The Environmental Degradation in the Earth Caused by Consumerism Culture In  Astro Boy The Movie.  Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies,  Universitas  Brawijaya. Supervisor: Yusri Fajar; Co-supervisor: Nurul Laili  Keywords: Astro Boy movie, consumerism culture, environmental degradation.   Nature is very crucial for all creatures on earth especially for human beings that always depend on nature in their daily life. By the time, what human gains from nature and what human does to restore the nature are not balanced and the effects can be felt gradually. Many ways human do to campaign and stop this phenomenon. Mass media such as movie is one of the interesting media to describe the earth’s conditions and it can be as the media object of research by using Ecocriticism theory. Astro Boy animated movie describes the environmental degradation caused by human’s bad behavior such as consumerism which causes waste.  This research is qualitative research and uses Ecocriticism  theory. In this research, the environmental degradation will be explained through the texts and pictures.  The findings of this research show the environmental degradation such as pollution, air and soil. Pollution has great effects for all creatures especially for human beings, short term or long term effects. Air pollution is caused by piles of waste that buried on the ground and make plants cannot grow. Plant is important for the air circulation. The effects of air pollution are irritation, respiratory infection, and even more serious are cancer, liver, heart disease, and so on. Besides air pollution, soil pollution also caused by piles of waste. The toxins elements through the air or rain water will be absorbed by the  ground and contaminate the ground water. Human whose consume the ground water that contaminated before will get great effects such as intestinal disease. For children, they will get serious effects, they potential to impair cognitive development, loss several IQ points and get mental retardation.  In sum, movie can be the media object to observe the phenomenon that happen in the world. To enhance the knowledge of Ecocriticsm, the further writer can use song as the media object to observe the phenomenon of environmental degradation.